Protection of Confidential Information in the Engineering Industry - Sadler, Pauline (2005)
This article explains how confidential information in the engineering industry can be protected by the common law action of breach of confidence and by confidentiality (secrecy) clauses in contract law. First the article discusses breach of confidence, examining cases such as Saltman Engineering Co Ltd v Campbell Engineering Co Ltd (1948) 65 RPC 203 and Surveys & Mining Ltd v Morrison [1967] VR 37. Then it discusses confidentiality clauses in contracts, and considers the nullifying effect of the doctrine of restraint of trade, looking at recent decisions such as Maggbury v Hafele (2001) 210 CLR 181 and AIM Maintenance v Brunt [2004] WASC 49.